2000
DOI: 10.1108/eb040128
|View full text |Cite
|
Sign up to set email alerts
|

Managing Customer Knowledge

Abstract: Becoming “customer‐centric” is easier said than done. But it can be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…Arthur Andersen Business Consulting (1999) indicated that the customer knowledge base is one of the top ten most important contributors to KM. Lesser, Mundel, & Wiecha (2000) have identified four approaches (customer knowledge development dialogues, customer knowledge communities, facilitating the capture of knowledge relevant data, and demonstrating enterprise leadership commitment to customer knowledge) that can expand the availability and use of customer knowledge. Lin (2000Lin ( /2001 presented a systemic integrated communications model that may help enterprises identify the potential issues of CRM.…”
Section: Knowledge-enabled Customer Relationship Managementmentioning
confidence: 99%
“…Arthur Andersen Business Consulting (1999) indicated that the customer knowledge base is one of the top ten most important contributors to KM. Lesser, Mundel, & Wiecha (2000) have identified four approaches (customer knowledge development dialogues, customer knowledge communities, facilitating the capture of knowledge relevant data, and demonstrating enterprise leadership commitment to customer knowledge) that can expand the availability and use of customer knowledge. Lin (2000Lin ( /2001 presented a systemic integrated communications model that may help enterprises identify the potential issues of CRM.…”
Section: Knowledge-enabled Customer Relationship Managementmentioning
confidence: 99%
“…Awareness of the significance of customer information is rapidly growing, and several mechanisms have been built to acquire this information (Lesser et al 2000). The perspective of relationship marketing, which is the oldest tradition in this area, has pointed out that using customers as informants enables customer segmentation and also increases the loyalty of customers (Zablah et al 2004;Grönroos 1990).…”
Section: Ways Of Acquiring Customer Informationmentioning
confidence: 99%
“…sales receipts data (Lesser et al 2000), what triggers companies to take a deep look for more interactive strategies of gaining an understanding of the customers in extended dialogs. However, customers might not be able to properly articulate their needs (von Hippel, 2005) or might not be willing to share their knowledge (Desouza et al 2008).…”
Section: Theoretical Background 21 State Of Customer Knowledge Manamentioning
confidence: 99%
“…Thus, only valuable, rare, imperfectly imitable and non-substitutable resources -regarded as strategic assets (Meso and Smith, 2000) -are the sources of firm's competitive advantage. While data is just a commodity, customer knowledge cannot be easily copied (Lesser et al 2000), which is a contributor to its competitive advantage (Bollinger and Smith, 2001).…”
Section: Customer Knowledge As a Strategic Asset: A Resource-based Viewmentioning
confidence: 99%